Efficiency in the Pediatric Emergency Department: A Choose Your Own Adventure for Pediatric Residents and Medical Students - Jessica Witkowski; Caroline Rassbach (Association of American Medical Colleges, 2015)
Abstract This 30-minute formative session seeks to provide key tools for triaging for medical students and residents in the pediatric emergency department. Via a case-based approach, the session presents basic clinical reasoning concepts in combination with tools for multitasking and prioritizing in the fast-paced environment that is a pediatric emergency department. Case-based scenarios create an emergency department setting where the learners have limited time, information, and resources to arrive at a decision. This provides a more realistic learning environment, which has been shown to produce successful outcomes of enhanced decision-making among students. The session has been successfully used with a range of learners from medical students to residents and attending physicians, helping to facilitate multiple levels of learning in a single setting and allowing novice students to learn from experts in the context of specific situations. This interactive, multiformat session has been given in two settings to a range of learners. Thirty-eight learners have provided feedback, and the demographics are included in the Instructor's Guide. From the first cohort of learners, the session received 100% positive feedback. Quantitative feedback was elicited from a second cohort of learners based on a scale of effective to ineffective. The cases and questions were found to be 100% effective. Comments included that the approach was "interactive," "clever," and "engaging." Using the envelopes to separate the cases was noted to "promote the autonomy of the learners" and encouraged learners to commit to responses. Seventy-seven percent of learners noted that "triage" and "ways to increase efficiency" were teaching points that came across clearly. Having multiple levels of learners in each small group allows for a think-aloud approach to reaching a group consensus, and large-group discussions give an opportunity for learners to receive feedback on their critical thinking. This lecture worked well in the setting of multiple levels of learners to help guide clinical decision-making in real-life scenarios.